Multiple Molecular Dynamics Simulations of the Inhibitor GRL-02031 Complex with Wild Type and Mutant HIV-1 Protease Reveal the Binding and Drug-Resistance Mechanism - Wang, Ruige (Langmuir : the ACS journal of surfaces and colloids, 2020)
Human immunodeficiency virus type 1 (HIV-1) protease is regarded as a fascinating target for drug development against HIV infection. However, mutations causing drug resistance severely limit the efficiency of the recently marketed drugs in the treatment of HIV replication. To elucidate the binding mechanism of HIV-1 protease with promising inhibitor GRL-02031 and further to probe the resistance mechanism associated with mutations (I47V, L76V, V82A, and N88D) to the inhibitor, we applied multiple molecular dynamics (MMD) simulations along with energy analysis by the molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) and solvated interaction energy (SIE) methodology on specific HIV-1 protease with GRL-0231 complexes. On the basis of detail analysis of the simulations, we revealed key characteristics that constitute the drug resistance of four mutation HIV-1 proteases toward GRL-02031: substitution of the side chain in these four mutation residues leads to a change in the distances between the flaps and catalytic sites, thereby reducing the affinity for GRL-02031 with these four mutation proteases, even though the L76V and N88D residues cannot directly contact GRL-02031. The results of energy analysis according to the MM-PBSA and SIE methods further indicated that hydrophobic interaction was considered to be the prime driving force for inhibitor GRL-02031 binding to protease and the decrease in van der Waals interactions between inhibitor GRL-02031 and mutant proteases as the primary cause of the drug resistance. Analyses of the hydrogen bonds and atomic interactions further provided detailed explanations for the resistance of these four mutation proteases toward inhibitor GRL-02031. The present study provides potential guidance on the structure-based inhibitors' design targeting HIV-1 protease